Pengembangan Multimedia Interaktif Fisika Berbasis Pendekatan STEM Pada Kelas XI SMA - Ramli Ramli; Rif'il Husniyah (Postgraduate, University of Mataram, 2023)
This development aims to produce a product in the form of interactive multimedia based on the STEM approach for class XI SMA. The results of this study can be accessed via an Android smartphone making it easier for students to study wherever and whenever. The development model used is the ADDIE development model with the stages of analysis, design, development, implementation and evaluation. At the analysis stage, an analysis of learning activities is carried out, an analysis of the needs of students and an analysis of learning media. The development stage uses the articulate storyline 3 application. As for the stages of development results, for instrument validation it is 0.97 with valid criteria and product validation is 0.78 in the valid category. While the results of practicality by students amounted to 83.96 and the results of practicality by educators amounted to 85.63 with a very practical category. For the effectiveness stage, there was an increase in mastery of knowledge competencies from 6,06% (Pretest) to 69,69% (posttest) while the percentage of students' completeness in skill competencies was 80.00%. For the results of the gain score, an average of 0.64 is in the medium category. Therefore interactive multimedia based on the STEM approach in class XI SMA is appropriate for use in the learning process.